PENGARUH PEER COACHING TERHADAP PRAKTEK PEMBELAJARAN IPA GURU SD (Studi Kuasi Eksperimen SD di Pekanbaru) - M. JAYA ADI PUTRA (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
This study investigates peer coaching as an alternative approach to improving teachers’ ability in conducting science learning in the classroom. The research was conducted in Pekanbaru with a total sample of eight teachers, who were divided into experimental and control groups. The results of the study indicate that peer coaching has a positive impact on the success of teachers’ inquiry practices, enabling them to implement and integrate all essential aspects of the science learning process more effectively.